Promoting instructional improvement or resistance? A comparative study of teachers' perceptions of teacher evaluation policy in Korea and the USA. Issue 5 (2nd September 2016) - Kim, Jihyun; Youngs, Peter
Abstract : This study draws on institutional theory to examine teachers' and principals' perceptions of new teacher evaluation policies, factors that influence such perceptions and how such perceptions shape the implementation of the policies in Seoul (Korea) and Michigan (USA). The study featured in-depth interviews of 11 elementary school teachers and 4 principals and analysis of policy documents in both countries. While Korean teachers strongly disagreed with the new teacher evaluation policy in Seoul and implemented it in ways that were not intended by policy makers, the Michigan teachers varied in their perceptions and implementation of the policies. The teachers' perceptions of the new policies seemed to be influenced by the designs of the policies, their backgrounds and definitions of 'effective teachers' and principal leadership. The association between teachers' perceptions and their implementation of the new policies was quite strong.